Juncker's Curse? Identity, Interest, and Public Support for the Integration of Core State Powers - Björn Bremer; Philipp Genschel; Markus Jachtenfuchs (JCMS: Journal of Common Market Studies, 2020)
In this study we analysed the patterns and covariates of public support for the European integration of core state powers based on an original new survey. We found considerable variation across integration instruments, member states and policy issues. Horizontal transfers are supported more than vertical capacity building; member states from the EU's South-East are more~supportive than states from the North-West; and support increases from debt relief to unemployment assistance, sharing the burdens of refugees, and military defence to disaster aid. Identity is a strong and fairly consistent predictor for individual variations in support. The association with respondents' interest is less consistent, but can be quite strong with respect to specific policy issues such as debt and unemployment. Overall, support for the integration of core state powers is higher and more variable than expected. This suggests there is considerable room for political agency rather than a general constraining dissensus.
Keywords: 330; capacity; core state powers; European integration; identity; interests; public opinion